2001
DOI: 10.1016/s0960-9822(01)00026-4
|View full text |Cite
|
Sign up to set email alerts
|

B-type cyclins CLB5 and CLB6 control the initiation of recombination and synaptonemal complex formation in yeast meiosis

Abstract: This assemblage of phenotypes reveals roles for CLB5 and CLB6 not only in DNA replication but also in other key events of meiotic prophase. Links between the function of CLB5 and CLB6 in activating meiotic DNA replication and their effects on subsequent events are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
100
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(107 citation statements)
references
References 44 publications
6
100
0
1
Order By: Relevance
“…Alternatively, a delay in the onset of premeiotic S phase in the mutant might affect DSB formation. It is shown that premeiotic S phase is tightly coupled with the formation of meiotic DSBs (16,27). However, we think these indirect effects are unlikely.…”
Section: Discussionmentioning
confidence: 80%
“…Alternatively, a delay in the onset of premeiotic S phase in the mutant might affect DSB formation. It is shown that premeiotic S phase is tightly coupled with the formation of meiotic DSBs (16,27). However, we think these indirect effects are unlikely.…”
Section: Discussionmentioning
confidence: 80%
“…Strong coupling between premiotic DNA replication and meiotic recombination has been reported in budding yeast (6)(7)(8)(9). Although premeiotic DNA replication is slightly delayed in hsk1-89 cells, evidence indicates that recombination and meiotic defects may not be consequences of incomplete DNA replication.…”
Section: Discussionmentioning
confidence: 89%
“…It is not known whether initiation is regulated by a common mechanism or the same set of replication origins is used during premeiotic S phase. In budding yeast, strong coupling of DNA replication and meiotic recombination has been shown (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…A high level of homologous recombination occurs after DNA replication but before the first meiotic nuclear division [meiosis I (MI)] (1,(3)(4)(5)(6)(7). Progression through meiosis is controlled by orchestration of the expression of various meiotic genes (8)(9)(10).…”
mentioning
confidence: 99%